Optimizing corn silage quality during hot summer conditions of the tropics: investigating the effect of additives on in-silo fermentation characteristics, nutrient profiles, digestibility and post-ensiling stability - Khan, Nazir Ahmad; Khan, Nadar; Tang, Shaoxun; Tan, Zhiliang (Frontiers in Plant Science, 2023)
Corn crop grown and ensiled at high temperature have lower water soluble carbohydrates (WSC), epiphytic lactic acid bacteria (LAB) population, lactic acid concentration, fermentation quality and aerobic stability. This study systematically investigated the effects of heterofermentative LAB (hetLAB), homofermentative LAB (homLAB), molasses and their mixture (MIX) on in-silo fermentation characteristics, chemical profiles, Cornell Net Carbohydrate and Protein System (CNCPS) carbohydrate subfractions, in vitro digestibility (DMD), microbial count, and post-ensiling aerobic stability of whole crop corn silage during hot summer (30 to 45°C) condition. Corn hybrids (P30K08 and DK6789) were ensiled at targeted dry matter (DM) of 330 g/kg for 0, 3, 7, 21, and 150 days in 3 L silos, without additive (CCS) or treated with hetLAB (4×106 cfu/g Lactobacillus buchneri), homLAB (1×106 cfu/g of L. plantarum), molasses (3% of fresh forage) or MIX (half of individual doses of homLAB, hetLAB and molasses) additives. The CCS, homLAB, hetLAB, molasses, or MIX treated chopped material of each hybrid were ensiled in 16 replicate silos at a density of 260 kg of DM/m3. Compared to CCS, the additives significantly improved silage nutritional and fermentation quality, DM digestibility (in vitro), count of LAB, DM recovery and aerobic stability, and decreased counts of yeast and mold. Among the inoculants, the homLAB and MIX inoculated silages had greatest improvement in fermentation quality and nutritional value. The homLAB produced corn silage with the highest (P < 0.05) content of lactic acid, and soluble carbohydrates, and lowest contents of acetic acid, NH3-N and pH, demonstrating desirable and restricted in silo fermentation. On the other hand, the hetLAB inoculated silages had the greatest (P < 0.05) value of acetic acids, highlighting greater aerobic stability. Interestingly, the MIX silages followed the hetLAB in acetic acid value and homLAB in lactic acid value. Notably, without additive stable pH was not achieved during 21 days, with application of molasses, hetLAB and the MIX inoculants stable pH was achieved during 7 days, and with homLAB stable pH was achieved during the first 3 days of ensiling. The greatest numbers of viable LAB were recorded in homLAB (8.13 log cfu/g) and MIX (7.89 log cfu/g) inoculated silages, while the lowest for CCS (6.29 log cfu/g). The lowest yeast (1.48 log cfu/g) and mold (0.22 log cfu/g) were recorded for hetLAB inoculated silage. The greatest (P < 0.05) DM recovery was recorded for hetLAB (97.3%) and MIX (96.9%), and the lowest for the control silage (92.9%). All additives significantly improved the aerobic stability of corn silage, and the greatest value of >72 h was recorded for hetLAB and MIX inoculats, and the lowest for CSC (25 h). In conclusion, additives application can improve fermentation quality, nutritional value, DM recovery and aerobic stability of whole crop corn silage under hot summer conditions of the tropics. The MIX inoculant showed potential to improve in-silo fermentation, and aerobic stability at the same time, however, further investigation are required, particularly with respect of dose rate.